2005
DOI: 10.1080/02652040400026400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additives on encapsulation efficiency, stability and bioactivity of entrapped lysozyme from biodegradable polymer particles

Abstract: Low encapsulation efficiency, incomplete and erratic release profiles are the most common features of controlled released protein delivery systems employing biodegradable polymers. In the present study, lysozyme as a model protein was encapsulated in biodegradable microspheres using solvent evaporation method and the effect of amphiphilic stabilizer, a basic salt and a lyoprotectant on microparticle formulation was evaluated. Incorporation rat serum albumin (RSA) in the internal aqueous phase during emulsion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 32 publications
0
30
1
Order By: Relevance
“…Enzyme activity before and after encapsulation and upon release can be monitored to investigate the effect of these processes on biological activity. Many researchers have estimated the bioactivity of LS by measuring the rate of degradation of Micrococcus luteus cells 25,46 . However, this method is not always reproducible because of the dependence on the ionic strength of the medium 47,48 .…”
Section: Enzyme Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme activity before and after encapsulation and upon release can be monitored to investigate the effect of these processes on biological activity. Many researchers have estimated the bioactivity of LS by measuring the rate of degradation of Micrococcus luteus cells 25,46 . However, this method is not always reproducible because of the dependence on the ionic strength of the medium 47,48 .…”
Section: Enzyme Bioactivitymentioning
confidence: 99%
“…This was calculated from the ratio of enzyme concentration determined from enzyme activity and the total enzyme concentration as determined by UV spectroscopy using the methods described below 25 .…”
Section: Encapsulation Efficiencymentioning
confidence: 99%
“…Encapsulation efficiency of alkaline phosphatase-loaded microspheres was 80.3 AE 1.3%, which is comparable to other optimized PLGA double emulsion systems. [30][31][32][33] High encapsulation efficiencies result in greater drug content in the microsphere product and minimize losses during the manufacturing process.…”
Section: Resultsmentioning
confidence: 99%
“…44 Although the time frame for release in this study was 3 months, the release rates for specific drug applications can be tuned to be shorter or longer by modifying various process parameters during microsphere preparation. These include changing the polymer lactide/glycolide ratio 45 or molecular weight, 46 introducing copolymers such as polycaprolactone 47 or additives such as poly(ethylene glycol), 33 or by simply altering microsphere size. 48 PLGA microsphere systems have been shown to be capable of degradation over timescales of a few weeks 46,49 to several months.…”
Section: Resultsmentioning
confidence: 99%
“…From previous studies it was concluded that by adjusting the phase volume ratio (Organic phase and External aqueous phase) and energy input in terms of sonication/homogenization, different size polymeric particles can be generated 23,26 . In this study the sonication time (40 % duty cycle for 3 minute) was increased and the phase volume ratio adjusted ( 26,28,29 . This suggested that these excipients mostly stabilize the aqueous/organic emulsion droplet during primary emulsification step of particle formulation.…”
Section: Discussionmentioning
confidence: 99%